Brand Awareness And Payment Ease to Create Customer Loyalty In The Strategy of Digital Marketing - Febriansyah; Anggalia Wibasuri (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: The rapid development of digital technology has driven a significant transformation in marketing strategies, particularly in utilizing digital marketing as a primary means of reaching and retaining consumers. Method: This study uses a qualitative approach with the aim of understanding in depth how brand awareness and payment ease play a role in shaping customer loyalty in digital marketing strategies. This approach was chosen because it is able to explore the meaning, perceptions, and subjective experiences of consumers that cannot be measured quantitatively. The informant selection technique was carried out using purposive sampling, with the criteria of respondents who actively use digital services (e-commerce or digital transaction-based applications). Data collection was carried out through in-depth interviews, observations, and documentation, in order to obtain rich and contextual data. Results: The combination of brand awareness and payment ease in the case study example can empirically build customer loyalty if carried out through an intermediary internet marketing system which is divided into certain payment zones to build relationships between customers and suppliers as a process in a digital marketing strategy.There are 5 critical factors in this research to build success between brand awareness and payment ease, namely 4 factors in customer interaction techniques with the internet, namely search engine optimization, social media marketing, content marketing and display marketingConclusion: All of these factors can build a good framework for creating customer loyalty in businesses in the current era of internet technology. Brand awareness serves as a cognitive foundation that influences consumer trust and preference for a brand, while payment ease acts as a functional factor that increases convenience and satisfaction during transactions. The integration of these two variables creates a holistic customer experience, ultimately driving repeat purchases and long-term loyalty. Therefore, companies need to develop digital marketing strategies that focus not only on increasing brand visibility but also on optimizing easy, fast, and secure payment systems to enhance business competitiveness and sustainability in the digital economy era.